Risk factors of postoperative infections in patients with iatrogenic gallbladder perforation during laparoscopic cholecystectomy - Shinya Urakawa; Toshiya Michiura; Shinji Tokuyama; Yasunari Fukuda; Yasuaki Miyazaki; Nobuyasu Hayashi; Kazuo Yamabe (Clinical Nutrition Open Science)
Summary: Background & Aims: Iatrogenic gallbladder perforation (IGP) frequently occurs during laparoscopic cholecystectomy (LC). The study aimed to investigate the risk factors including postoperative treatments (i.e., antibiotics and drainage) of postoperative infections in patients with IGP during LC. Methods: Of 539 patients underwent LC, 121 consecutive patients with IGP were enrolled retrospectively. Infectious complications were classified into surgical site infections, distant infections, and infections with unknown origin. The association between postoperative infections and clinical factors. Results: Of 121 patients, 20 patients (16.5%) had infectious complications. The infection-positive group of patients with IGP had a higher frequency of diabetes mellitus (positive vs. negative group = 50% (10/20) vs. 17.7% (18/101), P = 0.0018) and lower preoperative albumin (3.8 vs. 4.1 g/dL, P = 0.0081) than the infection-negative group. However, there were no associations between the presence of infectious complications and postoperative management for IGP such as antibiotics (positive vs. negative group = 35% (7/20) vs. 40.6% (41/101), P =0.64), drainage (45% (9/20) vs. 29.7% (30/101), P =0.12), and no treatment (20% (4/20) vs. 29.7% (30/101), P =0.38). Multivariate analysis showed that lower preoperative albumin (OR 4.90, 95% CI 1.20–20.0, P = 0.027) and the presence of diabetes mellitus (OR 5.49, 95% CI 1.62–18.6, P = 0.0063) were independent factors of infectious complications. Conclusions: Diabetes mellitus and preoperative malnutrition were associated with postoperative infections in patients with IGP during LC. On the other hand, postoperative management for IGP had no significant impact on the presence of infectious complications.